Influence of pH and ionic strength on the thermal gelation behaviour of pea protein. (February 2022) - Tanger, Caren; Müller, Michaela; Andlinger, David; Kulozik, Ulrich
Abstract: Gelation is one of the functional properties of protein, which can be controlled by pH and ionic strength. However, kowledge related to gelation properties of emerging plant proteins is still limited. In this paper, the solubility, the thermal behaviour and gelation behaviour of pea protein were analysed. Gels were analysed rheologically measuring the elastic modulus G′25°C, the ratio of G′25°C to G′95°C, and dependence on frequency and amplitude. In addition, the stabilizing protein interactions within the gel were analysed. The stiffest gels were obtained at pH 4.5 at 0.6 M NaCl. The high G′25°C and low tan δ value indicate the inclusion of active fillers, which is proposed to be insoluble protein. Salt addition at acidic pH could protect the protein from acid denaturation leading to a low heat denaturation at 62 °C–68 °C compared to heat denaturation at neutral pH. Addition of salt at pH 3 also led to a stiffer gel with a lower G′25 °C /G′95°C ratio, which indicates more hydrophobic and covalent interactions. An increase in ionic strength at pH 7 and pH 9 led to an increase of denaturation temperature above gelation temperature and an increase of electrostatic interactions. At pH 9 at ionic strenghts of 0.9 M NaCl and 1.5 M NaCl the frequency sweep showed that an entangled solution was formed, instead of a gel. It was observed that pea protein gelation were more influenced by the ionic strength at low pH values compared to neutral or alkaline pH. Graphical abstract: Image 1 Highlights: Ionic strength has a minor effect on gelation at neutral and alkaline pH and a major effect at acidic pH. Solubility impacts stiffness of pea protein gels. Gels at pH 9 and high ionic strength resemble rather entangled solutions than a gel. Stabilizing protein interaction are non-covalent and dependent on pH and ionic strength.